Potensi Anti Bakteri Ekstrak Bonggol Nanas Madu (Ananas Comosus L.Merr) terhadap Bakteri Aggregatibacter actinomycetemcomitans : The Potential of Honey Pineapple Extract (Ananas comosus L.Merr) Against Aggregatibacter actinomycetemcomitans Bacteria - Chasanah, Niswatun; Amiati, Devy; Dianawati, Nur; Septommy, Catur; Nurmalasari, Afrida; Firbanata, Mukhamad (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2025)
Periodontal disease can be caused by plaque bacteria. The plaque layer on the surface of the teeth is a biofilm containing an accumulation of microorganisms, including pathogenic bacteria, Aggregatibacter actinomycetemcomitans. Bromelain is an enzyme produced by pineapples (Ananas comosus L.Merr) and is found in higher concentrations in the core. The ability of bromelain to break down proteins inhibits the formation of bacterial cell membranes. Objective: To determine the antibacterial activity of pineapple core extract (Ananas comosus L. Merr) against Aggregatibacter actinomycetemcomitans. Research Method: This study is an in vitro laboratory experimental study. The study design used was a post-test only control group design. The study sample was Aggregatibacter actinomycetemcomitans bacteria obtained from the Microbiology Laboratory of the Faculty of Medicine, Airlangga University, Surabaya. Results : The Minimum Inhibitory Concentration (MIC) value was 0.78%, and the Minimum Bacterial Concentration (MBC) value was 6.25%. Conclusion: The pineapple stem extract (Ananas comosuis L. Meirr) exhibits potential antibacterial activity against the bacterial strain Aggregatibacterium actinomycetemcomitans.